Proceedings of the 16th EAI International Conference on Mobile and Ubiquitous Systems: Computing, Networking and Services 2019
DOI: 10.1145/3360774.3360780
|View full text |Cite
|
Sign up to set email alerts
|

Distances for wifi based topological indoor mapping

Abstract: For localization and mapping of indoor environments through WiFi signals, locations are often represented as likelihoods of the received signal strength indicator. In this work we compare various measures of distance between such likelihoods in combination with different methods for estimation and representation. In particular, we show that among the considered distance measures the Earth Mover's Distance seems the most beneficial for the localization task. Combined with kernel density estimation we were able … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Here, we use the Euclidean distance, i.e., dðx; yÞ:¼jjx À yjj 2 . Note that in theory a distance measure for compositional data such as the Aitchison distance (Martín-Fernández et al 1998) or one between probability distributions, e.g., those presented in Schaefermeier et al (2019), would be more suitable for our data. In our investigation, however, we found that the Euclidean distance leads to a better separation of venues into three different research fields, namely neural networks, information retrieval and general machine learning.…”
Section: Analyzing Venue Similarities Through Topical Mapsmentioning
confidence: 99%
“…Here, we use the Euclidean distance, i.e., dðx; yÞ:¼jjx À yjj 2 . Note that in theory a distance measure for compositional data such as the Aitchison distance (Martín-Fernández et al 1998) or one between probability distributions, e.g., those presented in Schaefermeier et al (2019), would be more suitable for our data. In our investigation, however, we found that the Euclidean distance leads to a better separation of venues into three different research fields, namely neural networks, information retrieval and general machine learning.…”
Section: Analyzing Venue Similarities Through Topical Mapsmentioning
confidence: 99%
“…Furthermore it provides a smooth distance estimate and hence robustness against random differences in the sampled RSSI observations. It has been shown in previous work [23], that between distributions separated by a large gap, EMD approximates the differences between their means. For overlapping distributions, on the other hand, it captures more subtle differences, e.g., between their variances and kurtoses.…”
Section: Distance Calculationmentioning
confidence: 83%
“…These steps can be seen as conceptual building blocks, which can be realized in different manners. The steps motion mode segmentation, likelihood estimation and distance calculation have been introduced and evaluated in previous work [23]. For completeness, we briefly sum up the recommended methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A landmark may be e.g. a payment terminal with a known location [18], or a room or any other indoor structure within a building [121]. Identifying and using landmarks as anchors helps in aligning collected dead-reckoning-based or radio-signal-based traces.…”
Section: Spatial Indoor Mappingmentioning
confidence: 99%